Thursday
March 23, 2017

Post a New Question

Posted by on Friday, July 18, 2008 at 12:04pm.

Prove the following identities:

a) (cosec θ + cotθ)(cosecθ - cotθ) = cotθtanθ


b) 2/(1 + sinθ) + 1/(1- sinθ) = (3sec^2)θ - tanθcosecθ


I basically just have to prove Left HandSide = Right Hand Side

  • math - , Friday, July 18, 2008 at 1:06pm

    (a) You should immediately recognize that the right side equals 1. If you don't, then review the relationship of tan and cot.

    Multiply out the two factors on the left and you get
    csc^2 θ - cot^2 θ) = 1

    Rewrite the left side as
    1/ sin^2 - cos^2/sin^2 = 1
    which is the same as
    (1 - cos^2)/sin^2 = 1
    1 = 1

    For (b), I suggest first rewriting the left side with a common denominator. Also recognize that tan*csc on the right equals sec = 1/cos

  • math - , Saturday, July 19, 2008 at 10:42am

    Thanks drwls that really helped !
    :)

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question